A Woman's War: A Novel - Deeping, Warwick, 1877-1950 (Salt Lake City, UT : Project Gutenberg, 2016)
"A Woman's War" by Warwick Deeping is a novel written in the early 20th century. The story centers around Catherine Murchison, a devoted wife, and her husband, James Murchison, a dedicated physician battling his personal demons and the pressures of his profession. Set in a small English town, the narrative explores themes of love, rivalry, and the complexities of human relationships, particularly the tensions that arise between Catherine and her rival, Mrs. Betty Steel. At the start of the novel, readers are introduced to Catherine Murchison, who returns home on a cold winter$1 (Bs night, depicted as a happy wife reflected in her comfortable domestic life. However, as the story unfolds, the backdrop of her husband James$1 (Bs struggles with the burdens of his career and inherited vices begins to emerge. Catherine's deep love for James motivates her to manage their home life while he fights the pressures of his medical career. Their relationship is complicated further by the presence of Betty Steel, who harbors jealousy and rivalry towards Catherine, creating an undercurrent of tension that hints at the challenges they will face. The opening sets a tone of domesticity laced with unease, inviting readers to delve into the intertwining lives of the characters. (This is an automatically generated summary.)s
Release date is 2016-08-04
Mardi Desjardins & the online Distributed Proofreaders Canada team
Keywords: City and town life -- Fiction; Physicians -- Fiction; Alcoholics -- Fiction; England -- Social life and customs -- Fiction; Husband and wife -- Fiction